Factors associated with partner notification of STIs in men who have sex with men on PrEP in France: a cross-sectional substudy of the ANRS-IPERGAY trial. (29th January 2018) - Suzan-Monti, Marie; Cotte, Laurent; Fressard, Lisa; Cua, Eric; Capitant, Catherine; Meyer, Laurence; Pialoux, Gilles; Molina, Jean-Michel; Spire, Bruno
Abstract : Objectives: Partner notification (PN) is a useful public health approach to enhance targeted testing of people at high risk of HIV and other STIs, and subsequent linkage to care for those diagnosed. In France, no specific PN guidelines exist and information about current practices is scarce. We used the ANRS-IPERGAY PrEP trial to investigate PN in HIV-negative men who have sex with men (MSM) reporting a bacterial STI. Methods: This substudy included 275 participants who completed a specific online PN questionnaire during the open-label extension study of the ANRS-Intervention Préventive de l'Exposition aux Risques avec et pour les Gays (IPERGAY) trial. Variables used as proxies of at-risk practices were defined using data collected at the previous follow-up visit about participants' most recent sexual encounter and preventive behaviours. χ 2 or Fisher's exact test helped select variables eligible for multiple logistic models. Results: Of the 275 participants, 250 reported at least one previous STI. Among the latter, 172 (68.8%) had informed their partner(s) of their most recent STI. Of these, 138 (80.2%) and 83 (48.3%) had notified their casual and main partners, respectively. Participants were less likely to notify their main partner when their most recent sexual encounter involved unsafe anal sex with a casual partner (adjusted OR (aOR) (95% CI) 0.18 (0.06 to 0.54), P=0.02). Older participants were less likely to inform casual partners (aOR (95% CI) 0.44 (0.21 to 0.94), P=0.03), while those practising chemsex during their most recent sexual encounter were more likely to inform their casual partners (aOR (95% CI) 2.56 (1.07 to 6.09), P=0.03). Conclusion: Unsafe sexual encounters with people other than main partners and street drugs use were two sociobehavioural factors identified, respectively, as a barrier to main PN and a motivator for casual PN, in a sample of high-risk MSM. These results provide an insight into current PN practices regarding STI in France and might inform future decisions about how to define feasible and acceptable PN programmes.